ERLINDUNGAN HUKUM TERHADAP ANAK KORBAN EKSPLOITASI SEKSUAL DITINJAU DARI ASPEK HUKUM PIDANA: Studi Kasus Pada Wilayah Hukum POLRES Lampung Timur Provinsi Lampung - Ermanita Permatasari (AS-SALAM, 2015)
Sexual exploitation of children is popularly called by CSEC or SexualExploitation of Children is a fundamental violation of the rights ofthe child. The infringement consisted of sexual abuse by adults, athird person, or others. The child is treated as a sexual object. Sexualexploitation of children is a form of coercion and violence againstchildren, and lead to forms of forced labor and slavery. Sexualexploitation of children is now becoming a matter of extreme concernthat has yet to be resolved. Sexual exploitation of children is a crimeagainst humanity that must be prevented and eliminated, because inaddition to violating the Convention on Rights of the Child (CRC), alsocontrary to religious and cultural norms.Criminal law protection of child victims of sexual exploitationembodied in Section 76 I and 88 Law of the Republic of IndonesiaNumber 35 of 2014 on the Amendment of Act No. 23 of 2002 onChild Protection. A form of legal protection for children as victimsof CSEC in the jurisdiction of Police of East Lampung, among othersProviding services optimally to the victim in the framework of thecomplaint and the disclosure of cases involving the victims, facilitatethe implementation of a post mortem on the victim, Concealingthe identity of the victim during the process of examination andFacilitating the process of assistance and rehabilitation to the victims.